Antenatal care utilization and compliance with national and WHO guidelines in rural Ethiopia: a cohort study - Meselech Roro; Wakgari Deressa; Bernt Lindtjørn (BMC, 2022)
Abstract Background Antenatal health care utilization has the potential to influence maternal and new-born health. In this study, we assessed compliance of antenatal care utilization with national and World Health Organization (WHO) guidelines. We also examined association of antenatal care utilization with adverse pregnancy outcomes as secondary outcome. Methods This was a community-based cross sectional study conducted from July 2016 to November 2017 in rural south-central Ethiopia. We described antenatal care received by pregnant women, whom we followed at three prescheduled visits during pregnancy and collected birth data at time of delivery. Extent of antenatal care content received, timing of antenatal care, place of antenatal care and place and mode of delivery were obtained and computed in accordance with national and WHO guidelines. For adverse pregnancy outcomes, computed as sum of low birth weight, preterm birth, intrauterine foetal death, and stillbirth, the exposure variable used was antenatal care utilization. Results Seven hundred and four (704) women participated in the study, and 536 (76.1%) had attended at least one antenatal care visit. Among women who attended antenatal care visit, majority, 421 (79.3%), had done so at health centres and hospitals, while 110 (20.7%) attended at health post. Average number of antenatal care visits was 2.5, which is less than that recommended in national and WHO guidelines. Only 18 (2.6%) women had attended antenatal care in their first trimester, which is low in contrast to the expected 100% specified in the guidelines. Less than half (47%) of the women delivered in a health facility. This is in contrast to the 100% expected health institution deliveries. Low birth weight was 7.9% (n = 48), and preterm birth was 4.9% (n = 31). There were 12 twin pregnancies, three stillbirths, 11 spontaneous abortions, and two intrauterine foetal deaths. We did not find significant association between adverse pregnancy outcomes and antenatal care utilization (COR = 1.07, 95% CI 0.62, 1.86). Conclusion This study showed that antenatal care service utilization in the study area was markedly low compared to that recommended in national and WHO guidelines. The obtained antenatal health care utilization was not associated with the registered adverse pregnancy outcomes.